2020
DOI: 10.1080/02786826.2020.1771270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propylene glycol, vegetable glycerin, and nicotine on emissions and dynamics of electronic cigarette aerosols

Abstract: An electronic cigarette (e-cig) generates aerosols by vaporizing the e-liquid, which mainly consists of propylene glycol (PG), vegetable glycerin (VG), and nicotine. Understanding the effects of e-liquid main compositions on e-cig aerosols is important for exposure assessment. This study investigated how the PG/VG ratio and nicotine content affect e-cig aerosol emissions and dynamics. A tank-based e-cig device with 10 different flavorless e-liquid mixtures (e.g., PG/VG ratios of 0/100, 10/90, 30/70, 50/50, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 69 publications
(95 reference statements)
8
26
0
Order By: Relevance
“…Surprisingly and in contrast, addition of nicotine alone to PG/VG led to reduced, yet non-significant, submicron and microparticle quantities coming from EC. This is consistent with other studies which showed emission of submicron 2.5 μm PM (PM 2.5 ) decreases with nicotine ( Li et al., 2020 ). We speculate that this may be attributed to hygroscopic nature of nicotine, which similar to PG/VG, has a low Log Kow (where Kow is n-octanol/water partition coefficient).…”
Section: Discussionsupporting
confidence: 93%
“…Surprisingly and in contrast, addition of nicotine alone to PG/VG led to reduced, yet non-significant, submicron and microparticle quantities coming from EC. This is consistent with other studies which showed emission of submicron 2.5 μm PM (PM 2.5 ) decreases with nicotine ( Li et al., 2020 ). We speculate that this may be attributed to hygroscopic nature of nicotine, which similar to PG/VG, has a low Log Kow (where Kow is n-octanol/water partition coefficient).…”
Section: Discussionsupporting
confidence: 93%
“…This is congruent with the vapor pressure of PG (0.13 mmHg at 25°C), lower than the VG one (1.68 × 10 −4 mm Hg at 25 °C), so that for the lower VG/PG ratio liquid, more solvent partitioned into the vapor phase. Such behavior is in agreement with the study of Li et al [ 29 ], who found that the VG/PG ratio was positively associated with the PM 2.5 emission factor. Moreover, according to the authors, nicotine also plays a role in reducing aerosol emissions.…”
Section: Resultssupporting
confidence: 93%
“…In addition, ratios for the mean PNC was 0.48 between Room V and Room N, indicating that 48% of the exhaled e-cig particles transported from Room V to Room N. In comparison, the ratio for mean PM 2.5 was only 0.12, suggesting fine particles transport much less than ultrafine particles. This is likely due to particle evaporation since our previous chamber study has shown higher loss rates of PM 2.5 (i.e., 4.4-7.0 h -1 ) compared to ultrafine particles (i.e., 0.6-1.2 h -1 ) (Li et al, 2020a). Particle evaporation led to a quicker decrease in particle mass compared with particle number.…”
Section: Transport Of Exhaled E-cig Aerosolsmentioning
confidence: 78%